Model Pembelajaran Pendidikan Agama Islam di SDN 2 Puliharjo Kecamatan Puring - Ayu Mujiati; Imam Subarkah; Oky Ristya Trisnawati (Tarbi: Jurnal Ilmiah Mahasiswa, 2023)
The importanc of teacher mastery of learning models that are in accordance with learning materials and student conditions to achieve a learning goal. The aims of this research are to find out what learning model is applied by Islamic Religious Education teachers at Elementary school 2 Puliharjo, Puring District. This research is a qualitative. Data was collected through observation, interviews, and documentation. Technique data analysis used is data reduction, data presentation, data veriication and conclusion drawing.Based on the results of research conducted in third graders Elementary school 2 Puliharjo, Puring District, it can be concluded that: (1) the learning model of Islamic Religious Education applied in Elementary school 2 Puliharjo is a cooperative learning model and a direct learning model.